Haptoglobin concentrations in cows with history of natural bracken fern chronic ingestion - Schmidt, Elizabeth Moreira dos Santos [UNESP]; Minozzo, Carolina Dutra; Perotta, Joao Henrique; Locatelli-Dittrich, Rosangela; Beltrame, Olair Carlos; Brum, Juliana Sperotto; Eckersall, Peter David; Barros Filho, Ivan Roque de (Univ Federal Santa Maria, 2024)
Bracken ferns (Pteridium spp.) have been associated with intoxication in cattle and is the cause of bovine enzootic hematuria (BEH) characterized by intermittent hematuria, anemia, and poor body condition. Acute phase proteins have not previously been investigated in detail in BEH. Thus, this investigation determined serum concentrations of haptoglobin, selected hematological (complete blood count and fibrinogen), biochemical (total serum protein, albumin, urea, creatinine, aspartate aminotransferase, gamma glutamyl transferase, and creatine kinase), and urinary analytes, in 50 Nelore cows from farms with history of natural bracken fern chronic ingestion in the southern region of Brazil. Twenty-nine cows had macrohematuria and 21 microhematuria. From the 29 cows with macrohematuria, 13 had a countless number of erythrocytes per high power macroscopic field and anemia. All cows had dipstick proteinuria. Median haptoglobin concentrations were elevated for 47 BEH cows with a 3.9-fold increase, suggesting a chronic inflammatory response while the number of total leukocytes and segmented neutrophils were above the reference intervals for 14 cows. Besides inflammation, there is a hypothesis that bracken fern could cause hemolysis in the circulation. Therefore, there could be a larger acute phase reaction but much of the haptoglobin was being removed as it was being produced. In our study, increases in haptoglobin, creatine kinase, hyperglobulinemia and anemia were found in cows with BEH, contributing to the understanding of the chronic inflammatory response which could be associated with neoplastic lesions in the urinary bladder caused by long-term and repeated ingestion of Pteridium species.
Keywords: Pteridium spp; haptoglobin; cattle; hematuria; acute phase proteins.